Amendments on the existing legislation pertaining to construction pollution in the Malaysian construction industry / Nur Afrina Qistina Ahmad Halmi - Ahmad Halmi, Nur Afrina Qistina (2019)
Pollution in constructions has recently become a severe menace globally with air, water, noise and waste pollution. The increase of pollution cases from construction projects in Malaysia is alarming and becoming one of the environmental problems. Despite extensive actions have been taken to curb these issues, there is no indication of reduction of cases. On that notes, there is a need to revisit the existing laws pertaining to pollution from construction projects. The existing legislations in Malaysia seem fragmented. The administration of environment in the country started from the coming into force of the Environmental Quality Act 1974. Other than that, there is environment-related legislation which is still in effect. It explains the strengths and weaknesses of environmental management. This research is to identify gap in the existing legislations pertaining to construction pollution. Therefore, three objectives have been formulated underpinned by stated aim which is to explore the existing legislations pertaining to construction pollution and to establish amendments to the existing legislations pertaining to construction pollution. The research was carried out qualitative approach. The research methodology was achieved by applying a thorough and well planned which is Doctrinal Research review and decipher the existing legislations and legal cases pertaining to construction pollution. Thus, Semi Structured Interviews were conducted to governing authorities relevant to construction pollution. The data was analysed to evaluate and determine the gap in the existing legislations in Malaysia. Lastly, amendments on the Environmental Quality Act 1974 and proposed government initiatives has been suggested in the research. Implementing good environmental practices and raising the awareness of constructions participants can minimise the pollution issues. The results of the study also suggested the recommendation to further amendment of the existing legislations pertaining construction pollution.